Partial Nephrectomy Versus Radical Nephrectomy for Clinical T2 or Higher Stage Renal Tumors: A Systematic Review and Meta-Analysis - Huang, Ruizhen; Zhang, Chiyu; Wang, Xing; Hu, Honglin (Frontiers in Oncology, 2021)
Objective： It remains controversial about the choice of a surgical method for clinically diagnosed T2 or higher stage kidney cancer. This article systematically reviewed the published comparative studies on the renal function, oncologic outcomes, and perioperative results of partial nephrectomy (PN) versus radical nephrectomy (RN) upon larger renal tumors (T2 and above), collecting these data and conducted a meta-analysis. Evidence acquisition： Searching from PubMed, Web of Science, and Embase, systematically reviewed the original studies on PN vs. RN in the treatment of T2 renal cancer were screened through strict literature inclusion and exclusion criteria. Rev Man5.4 software was used for data analysis of the perioperative results, renal function, and oncologic outcomes on the two surgical methods for T2 renal tumors therapy. Weighted mean difference (WMD) was used as the combined effect size for continuous variables, while odds ratio (OR) or risk ratio (RR) was used as the combined effect size for binary variables. Both types of variables use a 95% confidence interval (CI) to estimate statistical accuracy. Heterogeneity was low, the fixed-effects model was used to pool the estimated value; otherwise, the random-effects model was used when significant heterogeneity is detected. Results： 15 retrospective studies including 5,056 patients undergoing nephrectomy (PN: 1075, RN: 3081) were included in our study. Decline in eGFR after PN is lower ([MD: -11.74ml/min/1.73m2; 95% CI: -13.15, -10.32; p <0.00001]). The postoperative complication rate of PN was higher than that of PN ([OR:2.09;95% CI:1.56,2.80; p<0.00001]), and the postoperative overall survival (OS) of RN was higher than that of PN ([HR:0.77;95% CI:0.65,0.90; p=0.002]), and was the tumor recurrence ([RR:0.69;95% CI:0.53,0.90; p=0.007]). No obvious publication bias was found in the funnel chart of the overall survival rate of the two groups of patients. Conclusions： PN can benefit patients in terms of OS and renal function protection in terms of T2 renal tumors. However, although PN has advantages in T2-stage renal tumor therapy, it is also accompanied by a higher risk of surgical complications.